Simvastatin inhibits the pro-inflammatory and pro-thrombotic effects of IL-17 and TNF-α on endothelial cells. Issue 5 (21st August 2012) - Hot, Arnaud; Lavocat, Fabien; Lenief, Vanina; Miossec, Pierre
Abstract : Objectives: Statins are widely used for primary and secondary prevention of coronary atherosclerosis. Simvastatin, besides its lipid lowering properties, has various anti-inflammatory effects. The aim of this study was to assess whether simvastatin modulates the vascular effects of interleukin (IL)-17, an emerging actor in atherosclerosis. Methods: The effect of simvastatin was assessed in human umbilical vein endothelial cells treated by IL-17 alone or combined with tumour necrosis factor (TNF)-α, with or without mevalonate, an inhibitor of simvastatin. Its effects on IL-17-induced cytokine or chemokine expression were assessed at the mRNA level using qRT-PCR or protein level by ELISA. Its effect on the IL-17-induced pro-thrombotic state and cell invasion was assessed using a lumi-aggregometer and a Matrigel assay, respectively. Results: Simvastatin decreased IL-17-induced IL-6, IL-8, CX3CL-1, RANTES mRNA and CX3CL-1 and CCL20 production. Simvastatin restored the level of IL-33 mRNA which was decreased by IL-17. It reduced the expression of IL-17-induced pro-thrombotic genes such as tissue factor. Simvastatin restored the level of platelet aggregation to normal levels. Simvastatin enhanced the expression of CD39 and thrombomodulin mRNA initially reduced by IL-17 and TNF-α combination. Simvastatin suppressed IL-17-induced endothelial cells invasion. All these effects were reversed by the addition of mevalonate. Finally, simvastatin had an additive effect with infliximab to decrease the effect of the combination of IL-17 and TNF-α on IL-6 mRNA expression. Similar conclusion was obtained with rosuvastatin. Conclusions: Statins inhibit the pro-inflammatory, thrombotic and pro-aggregation effects of IL-17 on vessels. This provides a new understanding of the beneficial effects of statins in blood vessel inflammation.